Addressing the Adoption Gap: Exploring Resistance to Evidence-Based Practices among NCAA Coaches - Lawrence W Judge; Jeffrey Petersen; Olivia Huffman; Selen Razon (Journal of Applied Sports Management, 2024)
Athletic coaches strive to achieve optimal performance from their athletes and teams, yet many coaches fail to utilize new evidence-based practices (EBPs) with potential to improve performance. Many sport leaders and administrators seeking to assist and support positive change face resistance from coaches. This paper explores the lack of usage of EBPs among NCAA coaches and the subsequent effects on athlete performance and development. This problem is conceptualized through the theoretical underpinnings of diffusion of innovation theory and social cognitive theory. Application of resistance to change theories identifies action steps to help overcome barriers in the implementation of EBPs including limited resources, time constraints, and limited stakeholder support. To improve athlete development and promote sustainable sport participation, NCAA programs must overcome these barriers. This can be achieved by increasing coaches' access to information and resources, investing in their professional development, and supporting their adoption of sport-specific evidence-based practices.
Keywords: evidence-based practices; innovation; resistance; change